Expression of Bone Morphogenetic Protein-2 forMeasuring Effectiveness of Freeze Dried Bovine Bone Xenografts (FDBBX) Biomaterials as Bone ConnectorMaterial - Agus Purnomo; Dhirgo Adji (Jurnal Sain Veteriner, 2012)
Osteogenic activity  in  normal fracture  healing will start  early  at  around  1 week after  the  repair ,  but not necessarily occur in fracture healing with the aid of grafts. Demineralized freeze dried bovine bone xenograft (DFDBBX) is a bone graft material made from cows that are    widely produced recently to assist the process of bone  grafting  in  humans,  but  has  not  been  used  on  animals.  It  does  not  know  how  it  works  in  helping  to  repair  the bone.  T wenty male SD rats  weighing 150 g, were divided into  2 groups of 10 rats  each. Group I  was the  control group, the  rats  were fractured  and reconnected  immediately  using intramedullar  pin fixation,  Group II  was a group  of  rats  that  were    fractured  and  reconnected  immediately  using  pin  fixation  intramedular  plus  graft material of freeze dried bovine bone xenograft. Fracture of the left femur was made in diaphysis part of bone. Evaluation  of  joints  performed  regularly  at  1  week  ,  2  weeks,  4  weeks,  6  weeks  and  8  weeks  post  surgery respectively by selecting at random, each group of 2 rats. Rats at each observation were collected two  head / group,      rats    were  then  killed,  the  bone  parts  to  be  joined  was  taken  and  stored  in  10%  of  formalin  for histopathologic  examination.  Some  pieces  of  the  bones  were  used  for  the  analysis  of  bone  morphogenetic  protein 2 (BMP-2 ) by immunohistochemical method. The results were then analyzed descriptively to see the changes directly on the X-rays and tissue. Overall results of this study showed that the graft material of DFDBBX were osteocondusive  rather  than osteoinductive  properties.  Nevertheless,  the  biomaterial  is  useful  for  orthopedic purposes  primarily  of  handling  cases  with    partial  fracture  of  bone  tissue  which  is  lost.  Due  to  the  nature osteocondusive  of  DFDBBX  will  make  cells  to  grow  and  to  unify  the  separate  bone  fragments.Keywords  :  fracture,  osteogenic  activity ,  demineralized  freeze  dried  bovine  bone  xenograft,  bone morphogenetic  protein-2,  immunohistochemical  analysis